Improving Governance and Management of Health Systems : Partnerships and Observatories in Latin America and the Caribbean - Cortez, Rafael (World Bank, Washington, DC, 2014)
Public health observatories proactively investigate health issues to provide robust analytical evidence to policy makers. This type of organization has different characteristics from other public health institutions, such as information-gathering bodies, academic public health departments, or state employed public health practitioners. Governments in Latin America have also begun establishing regional, national, and provincial observatories. Some of the regional observatories provide comparisons of countries in the region in areas such as public health, human resources, food security, and nutrition. Regional and national health observatories have become important tools for governments and health ministries to support national strategic partnerships and to empower civil society, health sector stakeholders, and health sector authorities seeking to develop more effective and efficient health systems. Health observatories are therefore a key instrument for health systems to generate information, data, and intelligence on people's health status and the type and quality of health care delivery. By making all this information available to health providers and policy makers in a timely manner, the health observatories will ensure that their national health systems are results-oriented and engaged in a continuous process of improving quality and access.